The influence of Bi2O3 glass powder in the silver paste and the impact on silicon solar cell substrates. (15th February 2021) - Tsai, Jung-Ting; Lin, Li-Kai; Lin, Shun-Tian; Stanciu, Lia; Jun, Martin Byung-Guk
Abstract: The present work critically investigates the fabrication of metal contacts to advanced applications of bismuth-based oxide glass and screen-printed silver contacts for use in integrated circuits (I.C.s), solar cells, and sensors. Electrode contacts were fabricated by screen printing composite pastes composed of mainly silver powder, Bi2 O3 glass powder, and acyclic binder, and then firing the pastes in a belt furnace. The composite films' microstructures after firing at 830–890 °C were observed under various corrosion conditions, and the resulting layers were analyzed with X-ray diffraction (XRD) and the transfer length method (TLM). A series of investigations to determine the influence of Bi2 O3 glass in silver paste involved differential thermal analysis (DTA), scanning electron microscopy (SEM), electron probe X-ray microanalysis (EPMA), secondary ion mass spectrometry (SIMS), and transmission electron microscopy (TEM), to determine the effects of Bi2 O3 mixed with silver and the efficacy of the resulting metal contacts in I.C. fabrications. Results show that increasing firing temperature and the additive of Bi2 O3 glass controlled the silver's melting into the glass and influenced Ag crystallites' precipitation. Graphical abstract: Unlabelled Image Highlights: The influence of the Ag crystallites' size in Bi2 O3 glass are studied. The contact resistance of the silver layer and a single silver crystal is measured. The coated layer by layer microstructure was identified.